Creation as Gift: Stewardship and Sustainability in Catholic Theology - Laracy, Joseph R. (Theology and science, 2025)
This paper examines the Catholic understanding of creation and the ethical imperative to care for it, as rooted in the Catholic Intellectual Tradition, including social doctrine. It explores the theological concept of creation, humanity's role as stewards of creation, and the development of integral human ecology. Addressing contemporary concerns around pollution, climate, and sustainable energy, the paper suggests solutions such as nuclear power and space-based solar power while emphasizing the interconnectedness of environmental and human flourishing. It concludes by advocating for a holistic, interdisciplinary approach to address today's ecological crises in light of theology and modern science.